Ovarian teratomas: clinicopathological study at tertiary care center - Jagtap, Sunil Vitthalrao; Kshirsagar, Nitin S.; Jagtap, Shubham S.; Boral, Saswati; Nasre, Nitesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Teratomas are belonging to a group of germ cell tumors. It is also referred to as dermoid cyst. Teratomas are most common germ cell tumor of the ovary. Teratomas are composed of various histological types. In this article we are presenting various morphological patterns, its clinical manifestation and its clinical significance. Methods: This is prospective study for a period of 3 years from March 2016 to February 2019 at tertiary care hospital. It consists of total evaluation of 82 cases of ovarian lesions which were surgically excised for clinically or radiologically suspected of ovarian neoplasm. Results: A total of 82 cases of ovarian specimen were included out of which 18 cases were of ovarian teratoma. In these 17 cases were benign teratomas, 1 case of immature teratoma. All the cases of mature teratoma were predominantly of cystic type with focal solid areas. Right sided ovary was involved in44.5% cases while left sided in 55.5% cases. The tumor size ranges from 2.5 cm to 20.8 cms. The age range in this study was from 20 to 60 year. The common age observed for ovarian teratoma was in group of 31-40 years, having 6 cases. The clinically most of cases were asymptomatic or presented with unexplained abdominal pain or palpable mass. USG finding in most of cases were diffuse or partial echogenic mass lesion with cystic nature and echogenic bands. Conclusions: In our study showed mature cystic teratoma is the most common type of ovarian teratomas. The immature and monodermal types are rare. The histopathological examination plays important role in final diagnosis and patient management.